P0718HEALTH CARE COSTS IN CHRONIC KIDNEY DISEASE: A LONGITUDINAL STUDY FROM THE PIRP COHORT. (6th June 2020) - Rucci, Paola; Gibertoni, Dino; Voci, Claudio; Fantini, Maria Pia; Mandreoli, Marcora; Santoro, Antonio
Abstract: Background and Aims: Health care costs in patients with chronic kidney disease (CKD) vary widely according to patients' severity. In patients followed up in a community-based project, it is of interest to determine cost variations over time, as a result of treatment and CKD progression. The aim of the study was to estimate the costs incurred by the health care system for CKD patients in an Italian region. Method: Patients recruited in the Emilia-Romagna (Italy) PIRP project in the years 2007-2014 with CKD stage 3a to 5 were included in the study. Patients were stratified at baseline into 7 groups at different risk of progression according to the CT-PIRP classification (Rucci et al., A clinical stratification tool for chronic kidney disease progression rate based on classification tree analysis, NDT 2014). To calculate the annual medical costs, we multiplied the number of services used by the respective unit cost. Per capita costs were obtained dividing overall costs by person-years. We used DRG tariffs as a proxy of costs for hospital admissions, the regional nomenclator for outpatient visits and lab tests, and cost unit for prescribed drugs. Mixed effects generalized linear models were used to estimate the annual direct costs of CT-PIRP groups, adjusted for calendar year of entry in PIRP and local health authority of residence. Results: The study cohort includes 7737 CKD patients, aged 73.2±11.6 years, 64.5% males, mostly in CKD stage 4 (3136, 40.5%) and 3b (2799, 36.2%); 697 patients (9.0%) entered the study at stage 5. The CT-PIRP classification and frequency distribution is shown in Tab.1. After 4 years, 5017 (64.8%) were still alive, 1743 (22.5%) died, 546 (7.2%) were on ESKD and 422 (5.5%) were lost. The overall direct costs of patients while still enrolled in the PIRP project decreased from 36.89 million € in the first year to 32.22 in the fourth year, while the per capita annual median costs were stable around 2200 €. The cost breakdown showed a decrease of hospitalization and drugs costs and an increase in specialty visits costs (Fig.1). The model-estimated average annual costs were significantly higher for proteinuric, low GFR patients of CT-PIRP groups 2 and 3 (7239 € and 8825 € respectively), while non-diabetic, younger patients of group 5 determined a significantly lower burden (3350 €).